A Secure Chaotic Framework for Medical Image Encryption using a 3D Logistic Map - Adedokun, E A; Akan, Bello J; Salau, H B; Umoh, I J; Nwosu, Richard I; Ibrahim, Yunusa (Applications of Modelling and Simulation, 2020)
Information security and privacy are of utmost importance in transmitting, storing and preserving medical images. In this paper, a secure chaotic framework for medical image encryption is presented, in order to address existing defect in chaos-based image encryption algorithm. The proposed algorithm does the following: a 2D logistic adjusted sine map (2D-LASM) is utilized to generate random number with pixel format, the generated number are then inserted on a plain-image surrounding, which is then divided into non overlapping sub blocks. The scrambling sequence were generated using a 3D logistic map, before image pixel blocks scrambling and diffusion were performed on each sub-block of pixels  using the generated scrambling sequence. To verify the efficiency of the proposed algorithm, a number of simulations were carried-out. Based on the results obtained, the algorithm recorded an average score of 7.9998 for information entropy while for number of pixel change rate (NPCR) and unified average changing intensity (UACI) 99.6261% and 33.4830% respectively on an average scale. The proposed algorithm showed high robustness, sensitivity and resistance to all forms of differential attack.